Calculation of the input laser pulse radius's impact on stimulated Raman scattering under self-focusing conditions - Mokhonko, Оleksandr; Мохонько, Олександр; Іванісік, Анатолій (Київський національний університет імені Тараса Шевченка, 2024)
This study focuses on investigating stimulated Raman scattering under self-focusing conditions and the impact of other parameters on its efficacy.  Contrary to expectations, the efficiency of stimulated Raman scattering could discontinue to increase, and may rather start to decline when the input radiation power grows, because of the "absolute saturation" effect. The paper investigates the influence of this effect under self-focusing conditions using the example of a ruby laser in toluene. Calculations are given in order to characterize the indicated phenomenon based on power and Stokes component. The approaches for mitigating the impact of the "absolute saturation" effect on the process by increasing the initial radius of the incoming laser beam are being examined. A software product was developed using the Wolfram Mathematica program to enable calculations for each unique scenario. This software helps in selecting the settings to achieve the optimal parameters to ensure the highest efficiency of Raman scattering. Pages of the article in the issue: 169 - 172 Language of the article: English

Дана робота присвячена вимушеному раманівському розсіюванню за умов самофокусування, та впливу додаткових факторів на його ефективність. Всупереч очікуванням ефективність вимушеного раманівського розсіювання може перестати зростати, та й навіть почати спадати при збільшенні потужності вхідного випромінювання, через ефект ”абсолютного насичення”. В  роботі проводиться дослідження впливу даного ефекту за умов самофокусування  на прикладі рубінового лазеру в толуолі. Наводяться розрахунки для того аби охарактеризувати вказане явище на основі потужності й компоненти Стокса . Розглядаються  прийоми зменшення впливу ефекту ”абсолютного насичення” на процес в основі якого лежить збільшення початкового  радіусу вхідного  пучка лазера. На основі пакету Wolfram Mathematica створюється програмний продукт який дозволяє проводити обчислення для кожного конкретного випадку з метою підбору оптимальних параметрів для забезпечення оптимальної ефективності раманівського розсіювання.
Розрахунок впливу радіуса вхідного лазерного імпульсу на вимушене раманівське розсіювання за умов самофокусування
Keywords: stimulated Raman scattering; self-focusing; ”absolute saturation” effect; вимушене раманівське розсіювання; самофокусування; ефект ”абсолютного насичення”